2017
DOI: 10.4236/jcdsa.2017.74029
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Recurrent Aphthous Stomatitis by 100% Topical Pumpkin Seed Oil

Abstract: Background: Recurrent aphthous stomatitis (RAS) is a major oral health problem, where its etiopathogenesis is not well understood. Accordingly, its therapy whether topical or systemic can induce clearance, but the relapse rate is high. Objective: To use 100% topical pumpkin seed oil in RAS as it has many actions as anti-inflammatory and antioxidant effects. Patients and Methods: This single, blind, clinical, therapeutic trial was conducted in the Department of Dermatology-Baghdad Teaching Hospital, Baghdad, Ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Diversity types of therapies, both topical and systemic, have been used in treatment of RAU, including chlorhexidine, honey, topical, intralesional and oral steroids, dapsone, colchicine, and BCG …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Diversity types of therapies, both topical and systemic, have been used in treatment of RAU, including chlorhexidine, honey, topical, intralesional and oral steroids, dapsone, colchicine, and BCG …”
Section: Discussionmentioning
confidence: 99%
“…It is odorless or has a slight but not unpleasant odor and a mildly acidic taste in dilute aqueous solution. It has been used in treatment of many skin problems with antioxidant effect …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…97 Nigella sativa oil 100% and 5% zinc sulfate mouth wash also, can be used as a safe and effective topical treatment for ROA, with response rate 60.60% and 66.33% respectively. 98 A very recent Iraqi study had shown that 100% pumpkin seed oil is a new effective therapeutic and prophylactic agent in management of ROA. 99 Amylogulucosidase and glucose oxidase enzymes: have been used and show significant reduction in the number and pain of the ulcer.…”
Section: Topical Agentsmentioning
confidence: 99%